Effectiveness of a Protective Barrier for Aerosol Transmission Control during Oxygen Therapy with Different Devices - Hsiu-Mei Chang; Ben-Ran Fu; Hao-Wei Yu; Fu-Tsai Chung; Chen-June Seak; Ying-Chun Chen; Shih-Cheng Hu (Aerosol and Air Quality Research)
Abstract This study investigated the effects of an air extraction system or a protective barrier on aerosol leakage levels using experiments conducted inside the hospital negative-pressure isolation rooms. Patient simulators were tested with five different oxygen supply devices for aerosol dispersion tests: an endotracheal tube (ET), a non-invasive ventilation (NIV) mask, high-flow nasal cannula (HFNC), a simple mask, and a non-rebreather (NR) mask. The effects of nebulized drug delivery on aerosol concentration were also investigated. The results showed that aerosol concentration was generally higher after using nebulized drug delivery than without it. For cases with HFNC and simple and NR masks, the aerosol concentrations were relatively higher, usually one to two orders of magnitude greater than those in cases with ET and NIV masks. Experiments using solely protective barrier (Case C) showed higher improvements in aerosol leakage than those using only the air extraction system (Case B); however, aerosol accumulation within the protective barrier remains an issue. In cases (Case D) using both the air extraction system and a protective barrier, the improvements were the highest, with some values even exceeding 99%; additionally, the aerosol concentration within the protective barrier was reduced. This could potentially reduce the risk of infection for healthcare workers during clinical applications. In summary, the ability to prevent aerosol leakage is ranked as follows: Case D > Case C > Case B.